PENGARUH KOMITMEN DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT. ATOZ MEGA INDONESIA - Lulu Octaviani, Lulu Octaviani; Achmad Jaelani, Achmad Jaelani; Hasanuddin, Hasanuddin (Cakrawala Akuntansi & Manajemen, 2024)
How much does commitment affect PT employees' performance. Atoz Mega Indonesia? How much does loyalty affect PT employees' performance. Atoz Mega Indonesia? How much do commitment and loyalty affect PT employees' performance. Atoz Mega Indonesia? The research was conducted at PT. Atoz Mega Indonesia Jl. Raya Kodau No.19 Jatirahayu, Kec. Pondok Melati – Bekasi City using a survey method. The research population consisted of all employees at PT. Atoz Mega Indonesia. Data collection techniques in research use questionnaires, distributing questionnaires to research subjects aimed at obtaining data or information about research problems, questionnaires distributed to respondents in the form of questionnaires in the form of questions that ask respondents to choose answers. Testing data quality using validity and reliability tests. Data were analyzed using correlation analysis and linear regression, T-test, F test, coefficient of determination test, and accompanied by classical assumption test. The correlation analysis and multiple linear regression results indicate that work commitment and loyalty are positively and significantly related to employee performance at PT. Atoz Mega Indonesia is indicated by the number of positive correlation coefficients. The results of the T-test explain that work commitment and work loyalty individually affect employee performance at PT. Atoz Mega Indonesia shows that the significant number for each variable is below 0.05. The results of the F test explain that Work Commitment and Work Loyalty together have a positive and significant effect on Employee Performance at PT. Atoz Mega Indonesia, this is indicated by the significant number produced below 0.05. Based on the results of the coefficient of determination, it can be explained that there is an influence of Work Commitment and Work Loyalty on Employee Performance at PT. Atoz Mega Indonesia by 86.9%.